2016
DOI: 10.1016/j.phrs.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A selective alpha1D-adrenoreceptor antagonist inhibits human prostate cancer cell proliferation and motility “in vitro”

Abstract: The progression of prostate cancer (PC) to a metastatic hormone refractory disease is the major contributor to the overall cancer mortality in men, mainly because the conventional therapies are generally ineffective at this stage. Thus, other therapeutic options are needed as alternatives or in addition to the classic approaches to prevent or delay tumor progression. Catecholamines participate to the control of prostate cell functions by the activation of alpha1-adrenoreceptors (alpha1-AR) and increased sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…90,91 Consistently with affinity data, functional studies of the antagonist activity at the 1A-, 1B-and 1D-ARs show that the two combined modifications, fusion of cyclohexane at the benzodioxane and of benzene at the 2,6 dimethoxyphenyl, lead to a potent and selective 1A-AR antagonist (compound 8) (7.98 1A pA2 vs <5 1B pA2 and 5.59 1D pA2) (Figure 6). 89 On the other hand, selective 1D-AR antagonist activity is attained by maintaining the characteristic ortho hetero-disubstituted phenyl group of (S)-WB-4101, but rigidified in the 6-methoxy-2,3-dihydrobenzofuran substructure (9.58 1D pA2 vs 8.49 1B pA2 and 7.88 1A pA2), 92,93 while 8-substitution at the benzodioxane, in particular with methoxyl, confers significantly selective 1B-AR antagonism (9.58 1B pA2 vs 8.55 1A pA2 and 7.93 1D pA2) (compounds 9 and 10) (Figure 6). 94 (S)-WB4101, 7 and 9 show also intrinsic relaxant activity on non-vascular smooth muscle and moderate negative inotropic effect, which parallel the calcium antagonist effects suggesting a direct interaction with L-type Ca 2+ channels.…”
Section: Benzodioxanes As 1-adrenoceptors Antagonistsmentioning
confidence: 99%
“…90,91 Consistently with affinity data, functional studies of the antagonist activity at the 1A-, 1B-and 1D-ARs show that the two combined modifications, fusion of cyclohexane at the benzodioxane and of benzene at the 2,6 dimethoxyphenyl, lead to a potent and selective 1A-AR antagonist (compound 8) (7.98 1A pA2 vs <5 1B pA2 and 5.59 1D pA2) (Figure 6). 89 On the other hand, selective 1D-AR antagonist activity is attained by maintaining the characteristic ortho hetero-disubstituted phenyl group of (S)-WB-4101, but rigidified in the 6-methoxy-2,3-dihydrobenzofuran substructure (9.58 1D pA2 vs 8.49 1B pA2 and 7.88 1A pA2), 92,93 while 8-substitution at the benzodioxane, in particular with methoxyl, confers significantly selective 1B-AR antagonism (9.58 1B pA2 vs 8.55 1A pA2 and 7.93 1D pA2) (compounds 9 and 10) (Figure 6). 94 (S)-WB4101, 7 and 9 show also intrinsic relaxant activity on non-vascular smooth muscle and moderate negative inotropic effect, which parallel the calcium antagonist effects suggesting a direct interaction with L-type Ca 2+ channels.…”
Section: Benzodioxanes As 1-adrenoceptors Antagonistsmentioning
confidence: 99%
“…The contradictory results may be due to different tissue specificities. Ca 2+ protein alpha 1D is expressed in a variety of malignant tumors and promotes tumor progression [ 52 ]. Inhibiting NCX1/3 and promoting the release of calcium from the endoplasmic reticulum can increase [Ca 2+ ]i, upregulate Ca 2+ protein alpha 1D, and promote the migration of HCT116 colon cancer cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, naftopidil cytostatic and cytotoxic properties are reached at high concentrations in vitro and reducing effective concentrations through more effective compounds would facilitate is use in clinic. It is interesting to note that Colciago et al, synthesised a compound derived from WB4101: A175, that binds with a strong affinity α 1D -AR [ 98 ]. They demonstrated that this compound had an anti-proliferative effect in androgen-insensitive prostate cancer cells PC3 that strongly expressed α 1D -AR at the mRNA level but had no effect on DU145 cells that did not express this receptor.…”
Section: Discussionmentioning
confidence: 99%